Magnetic Suppression of Perceptual Accuracy Is Not Reduced in Visual Snow Syndrome - Eren, Ozan E.; Ruscheweyh, Ruth; Rauschel, Veronika; Eggert, Thomas; Schankin, Christoph J.; Straube, Andreas (Frontiers in Neurology, 2021)
Objective: Patients with visual snow syndrome (VSS) suffer from continuous (“TV snow-like”) visual disturbance of unknown pathoetiology. In VSS, changes in cortical excitability in the primary visual cortex and the visual association cortex are discussed, with recent imaging studies tending to point to higher-order visual areas. Migraine, especially migraine with aura, is a common comorbidity. In chronic migraine and episodic migraine with aura but not in episodic migraine without aura, a reduced magnetic suppression of perceptual accuracy (MSPA) reflects a probably reduced inhibition of the primary visual cortex. Here we investigated the inhibition of the primary visual cortex using MSPA in patients with VSS, comparing that with MSPA in controls matched for episodic migraine. Methods: Seventeen patients with VSS were compared to 17 age- and migraine-matched controls. Visual accuracy was assessed by letter recognition and modulated by transcranial magnetic stimulation delivered to the occipital cortex at different intervals with respect to the letter presentation (40, 100, and 190 ms). Results: Suppression of visual accuracy at the 100-ms interval was present without significant differences between VSS patients and age- and migraine-matched controls (percentage of correctly recognized trigrams, control: 46.4 ± 34.3; VSS: 52.5 ± 25.4, p = 0.56). Conclusions: In contrast to migraine with aura, occipital cortex inhibition, as assessed with MSPA, may not be affected in VSS.